2021
DOI: 10.3390/pathogens10111397
|View full text |Cite
|
Sign up to set email alerts
|

The Flo Adhesin Family

Abstract: The first step in the infection of fungal pathogens in humans is the adhesion of the pathogen to host tissue cells or abiotic surfaces such as catheters and implants. One of the main players involved in this are the expressed cell wall adhesins. Here, we review the Flo adhesin family and their involvement in the adhesion of these yeasts during human infections. Firstly, we redefined the Flo adhesin family based on the domain architectures that are present in the Flo adhesins and their functions, and set up a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 378 publications
(530 reference statements)
0
22
0
Order By: Relevance
“…Six of those were chosen along the ranked 71 homologs in gaps of 10 (starting from C. dubliniensis orthologs located five places away from the original C. albicans Als5). To these six, we added the emerging pathogen Candida auris, which was not a part of the homologs collected by the ConSurf webserver due to low sequence identity to the C. albicans Als5p (Willaert, 2018;Willaert et al, 2021). The multiple sequence alignment of the 71 homologs along with the C. auris sequence was obtained by reproducing the ConSurf search with similar parameters but lower sequence identity of 25%-95%, and then filtering out the irrelevant homologs using Jalview2.…”
Section: Calculation Of Evolutionary Conservation Using the Consurf/c...mentioning
confidence: 99%
“…Six of those were chosen along the ranked 71 homologs in gaps of 10 (starting from C. dubliniensis orthologs located five places away from the original C. albicans Als5). To these six, we added the emerging pathogen Candida auris, which was not a part of the homologs collected by the ConSurf webserver due to low sequence identity to the C. albicans Als5p (Willaert, 2018;Willaert et al, 2021). The multiple sequence alignment of the 71 homologs along with the C. auris sequence was obtained by reproducing the ConSurf search with similar parameters but lower sequence identity of 25%-95%, and then filtering out the irrelevant homologs using Jalview2.…”
Section: Calculation Of Evolutionary Conservation Using the Consurf/c...mentioning
confidence: 99%
“…Evaluation of biofilm formation and adherence in C. krusei led to the formation of floating biofilms and flocs, phenotypes that in S. cerevisiae are associated with the expression of flocculins in the cell wall (27). The flocculin (Flo) family of S. cerevisiae includes homologous Flo1, Flo5, Flo9 and Flo10 lectins that promote cell-cell adhesion by binding to mannose, which may lead to floc formation.…”
Section: Discussionmentioning
confidence: 99%
“…For the non-CTG clade pathogenic yeast Candida glabrata similar genomic studies demonstrated that it contains an extraordinarily large number of more than 70 sequences encoding GPI-modified adhesin-like proteins (21)(22)(23)(24)(25). Recent structural studies showed that most of these adhesins can be divided into two groups: (i) Epa1-related proteins with shown or presumed host-binding lectin activities and containing N-terminal PA14-like domains similar to flocculins in S. cerevisiae (26,27), and (ii) proteins with β-helix/βsandwich N-terminal domains for which the substrate ligands are still unidentified although involvement in adherence to polystyrene surfaces was demonstrated for Awp2 (28).…”
Section: Introductionmentioning
confidence: 99%
“…Six of those were chosen along the ranked 71 homologs in gaps of 10 (starting from C. dubliniensis orthologs located five places away from the original C. albicans Als5). To these six, we added the emerging pathogen Candida auris , which was not a part of the homologs collected by the ConSurf webserver due to low sequence identity to the C. albicans Als5p (54, 55). The multiple sequence alignment of the 71 homologs along with the C. auris sequence was obtained by re-producing the ConSurf search with similar parameters but lower sequence identity of 25-95%, and then filtering out the irrelevant homologs using Jalview2.…”
Section: Methodsmentioning
confidence: 99%